2023
DOI: 10.1021/acs.inorgchem.2c04072
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-Incorporated Porphyrin-Based Porous Organic Polymer for a Nonenzymatic Electrochemical Glucose Sensor

Abstract: To date, the fabrication of multifunctional nanoplatforms based on a porous organic polymer for electrochemical sensing of biorelevant molecules has received considerable attention in the search for a more active, robust, and sensitive electrocatalyst. Here, in this report, we have developed a new porous organic polymer based on porphyrin (TEG-POR) from a polycondensation reaction between a triethylene glycol-linked dialdehyde and pyrrole. The Cu(II) complex of the polymer Cu-TEG-POR shows high sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…As a new class of exceptional materials, two-dimensional (2D) conjugated organic polymers (COPs) with amorphous extended p-conjugated networks offer the desirable properties and functions with a wide range of applications in catalysis, [1][2][3] sensors, 4,5 and gas storage 6 and separation. 7 Their multifunctional networks are constructed through homo-or heteropolymerization between organic linkers, which are formed by covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…As a new class of exceptional materials, two-dimensional (2D) conjugated organic polymers (COPs) with amorphous extended p-conjugated networks offer the desirable properties and functions with a wide range of applications in catalysis, [1][2][3] sensors, 4,5 and gas storage 6 and separation. 7 Their multifunctional networks are constructed through homo-or heteropolymerization between organic linkers, which are formed by covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Though several covalent organic polymer electrocatalysts have also been developed, due to their lower electrical conductivity, the addition of external additives (mostly carbon materials) or thermal annealing is a must in most of the cases as they provide a graphitic base that gives the material necessary conductivity and electrochemical sites. However, such materials are often not given much importance due to their additional cost. Combining electroactive metalloporphyrins in the polymeric skeleton of the covalent organic polymers could be an efficient strategy for developing efficient annealing-free electrocatalysts. …”
Section: Introductionmentioning
confidence: 99%
“…Cao et al showed OER and ORR activities of metal-corrole-based POP . There are other examples, where researchers have put efforts into designing some noble metal-based catalysts. In our recent efforts to explore the catalytic activity of porphyrin-based polymers, we have reported a urea oxidation reaction (UOR) and nonenzymatic glucose sensing using metal-incorporated porphyrin-based polymers.…”
Section: Introductionmentioning
confidence: 99%